Development of small and efficient ozone generators using corona discharge; Korus 2001; Vol. 1 - Jae Seok Park; Kwang Ho Kim; Gyu Jin Kwon; Lukanin A.; Khasanov O. L. Oleg Leonidovich; Young Soo Kim; Jae Shin Lee (2001, 2001)
This paper describes the development of small and high efficient ozone generators using a corona discharge plasma. We carried out ozone generation tests with varying parameters including the flow rate of the feeding gas, the composition of the feeding gas, discharge gap, dielectric thickness, and impulse frequency. The feeding gas composition greatly affected the ozone generation rate, which was increased in an order of ambient air, dry air, and pure oxygen. With increasing the gas flow rate, the ozone generation rate was enhanced while the ozone concentration was decreased. An optimized condition for ozone generation was achieved at a frequency of 4 kHz, a discharge gap of 0.5 mm and a feeding gas pressure of 0.5 kgf/cm2.